Understanding Corporate Vulnerabilities in Latin America - Caceres, Carlos (IMF Working Papers; Working Paper ;, 2016)
This paper analyzes the potential risks and vulnerabilities of non-financial corporates in Latin America and Canada. We quantify the impact of company-specific, countryspecific, and global factors in driving corporate spreads. Overall, we found that all these factors play a role in explaining corporate risk. In particular, country specific factors such as exchange rate and sovereign CDS spreads are significantly associated with changes in corporate spreads, underscoring the importance of solid policy frameworks. We also find that global conditions, such as the VIX, are dominant drivers of corporate spreads. In recent years, the adverse effects from deteriorating domestic conditions have been broadly offset by relatively bening global financial conditions. However, a sustained reversal in these conditions would put significant pressure on corporate risk.